Pendidikan Bagi Anak Jalanan Usia Sekolah Dasar Di Kota Makassar - Amrullah Mahmud; Rahmah Kumullah; A. Zam Immawan Alam (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2020)
This research as a porpose (i) to know illustration and establishment expanding education access for street childreen of elementary school in makassar (ii) Knowing  what obscacles pased by institute providers of education access for street chidreen of elementary school in makassar. The research methads used in this research is qualitative descriptive. The technique of collecting data through observation, interviews, and documentation. The subject is the institute/foundation in particular education of street childreen with social departement in makassar as a center of information about street childreen. The resuls of illustration that indicate education of street children of elementary shool in makassar still having some obstacles such as, lact of socialization to society about the importance of education especially low-income society, lack of facilities and infrastructure owned by non formal education in teaching and learning process, there is no legal basis (UU) which regulates the sanctions agains children which is located on the roadside, there is no UU governing the imposition of sanctions to parents who employ children which is still elementary school (SD) Handling Makassar street children still do not have model yet and the appropriate approach in haldling multi-system base. Handling has been largely ineffective. Seen by parenting tend to be unproductive.